(untitled) (Research, Society and Development, 2021)
The objective of this work was to describe the development of a mobile application to promote the occupational health of health professionals in a university hospital. This is a methodological study with a participatory interface, technological production, carried out from the steps of textual elaboration of the available material, mapping of requirements, and prototyping of system screens and development of the first version. The By Your Side (BYS) application is an occupational health promotion tool, available free for Android and iOS. Among the proposed activities, nutritional guidance, exercise, relaxation techniques, mental health care, guidance on professional assistance, dissemination of programs of the institution, medication alerts, and calculators for the Mass Index stand out. Body (BMI) and water intake, entertainment, journaling and forum with groups and rooms. The application makes available the locations, available days and service flows with professionals to facilitate user access and adherence. It is concluded that BYS has the potential to help health professionals, promoting a healthier life, relieving the work stress load, through various activities related to physical and mental health.